PERBEDAAN GAYA BELAJAR ANTARA TIPE KEPRIBADIAN INTROVERT DAN EKSTROVERT PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - MUHAMMAD HENDARTA; DESI ISNAYANTI (LP2MTBM MAKARIOZ, 2021)
Students have different learning styles. The component that affects learning styles is personality type because a person'spersonality is different to be comfortable in learning. Knowing learning styles is important in learning success because theybetter know one's strengths and weaknesses. This study aims to determine the differences in learning styles betweenintrovert and extrovert personality types among FK UMSU students. This study was a descriptive analytic study with a crosssectional design. The research sample consisted of 135 students of FK UMSU class 2019 who were taken using the simplerandom sampling method. This research was tested by using the Kolmogorov-Smirnov test. Overall, the results showed thatthe dominant learning styles of students were auditory learning styles (33.3%). Then the description of the dominantpersonality type is the introvert personality type (84.4%). Kolmogorov-Smirnov test analysis obtained p value 0.907, whichmeans there is no difference in learning styles with personality types. There is no difference between learning styles andpersonality types in FK UMSU students.